2016
DOI: 10.3168/jds.2015-10697
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study for longevity with whole-genome sequencing in 3 cattle breeds

Abstract: Longevity is an important economic trait in dairy production. Improvements in longevity could increase the average number of lactations per cow, thereby affecting the profitability of the dairy cattle industry. Improved longevity for cows reduces the replacement cost of stock and enables animals to achieve the highest production period. Moreover, longevity is an indirect indicator of animal welfare. Using whole-genome sequencing variants in 3 dairy cattle breeds, we carried out an association study and identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
40
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 39 publications
5
40
0
1
Order By: Relevance
“…Thus, Screening and identifying susceptibility or resistance genes associated with mastitis traits will improve the properties of dairy cow populations and is worthwhile to reduce the incidence of mastitis (SAHANA et al 2014;KADRI et al 2015;WANG et al 2015). Different research strategies successfully used to identify significant genes associated with the mastitis traits, including SNP in a candidate gene, quantitative trait loci (QTL) and GWAS (BRONDUM et al 2015;POKORSKA et al 2016;ZHANG et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, Screening and identifying susceptibility or resistance genes associated with mastitis traits will improve the properties of dairy cow populations and is worthwhile to reduce the incidence of mastitis (SAHANA et al 2014;KADRI et al 2015;WANG et al 2015). Different research strategies successfully used to identify significant genes associated with the mastitis traits, including SNP in a candidate gene, quantitative trait loci (QTL) and GWAS (BRONDUM et al 2015;POKORSKA et al 2016;ZHANG et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Sahana and his colleagues reported two clinical mastitis candidate genes (vitamin D-binding protein precursor, GC and neuropeptide FF receptor 2, NPFFR2) using high-density single nucleotide polymorphic array and WGAS (SAHANA et al 2014). These two candidate genes detected to associate with mastitis traits in dairy cows through genomic sequencing in 2016 (ZHANG et al 2016). In 2015, Wang et al identified another two mastitis susceptibility genes (TRAPPC9 and ARHGAP39) in Chinese Holstein .…”
Section: Introductionmentioning
confidence: 99%
“…Associations of common genetic variants with complex diseases and quantitative traits have been successfully identified in humans and livestock [ 1 3 ]. However, these loci explain only a small fraction of the total genetic variance of a trait.…”
Section: Introductionmentioning
confidence: 99%
“…It can identify the quantitative trait loci (QTL) regions and candidate genes that affect the traits of interest. In dairy cattle, the GWAS of production traits, such as milk yield, fat yield, and protein yield, (Maxa et al, 2012;Minozzi et al, 2013;Nayeri et al, 2016;van den Berg et al, 2016); functional or fertility traits, such as calving to the first service interval, days open, non-return rate, and conception rate (Olsen et al, 2011;Minozzi et al, 2013;Nayeri et al, 2016;Parker Gaddis et al, 2016); health traits, such as clinical mastitis and udder type (Flury et al, 2014;Sahana et al, 2014); and longevity (Zhang et al, 2016), have been reported. A previous GWAS showed that the DGAT1 gene on bovine chromosome BTA14 was associated with milk production and the FAM1818 gene on BTA21 was associated with days open (Minozzi et al, 2013;Nayeri et al, 2016).…”
Section: Introductionmentioning
confidence: 99%